Portal hypertension in dogs - Sartor, Raquel [UNESP]; Mamprim, Maria Jaqueline [UNESP] (Univ Federal Rural Pernambuco, 2011)
Portal hypertension (PH) is the pathological increase in portal vein pressure above normal limits. Two variables control the pressure in the portal system: the resistance to blood flow and blood flow volume in the portal system. If one these variables changes, PH may develop. Classification: Pre-hepatic (e. g. compression of the portal vein), intrahepatic (e. g. chronic hepatitis and cirrhosis) or post-hepatic (e. g. right heart failure). The invasive methods (intravenous catheter) were replaced by an indirect method of diagnosis: Doppler Ultrasound. This technique does not measure portal pressure, but indirectly allows the diagnosis of PH. Average speed of portal flow decrease (<10 cm/s) and hepatofugal flow have been reported in cirrhotic dogs with PH. Currently, the focus of the ultrasound is the detection of acquired collateral portal circulation (ACPC), closely correlated with hepatic encephalopathy. The characterization of these vessels is essential to differentiate them from congenital shunts. They are usually multiple vessels, small and tortuous, with turbulent flow, near to the kidneys, and/or a single and larger vessel, draining into the left renal vein (dilated gonadal vein). Gastric, esophageal and mesenteric varices may occur. After identifying the PH, it is important to determine its origin in order to treat the underlying disease. B-Mode Ultrasound and Doppler are the best choices in cases of suspected PH, because they may recognize not just the hypertension, but also its complications and origin.
Keywords: hemodynamic; portal vein; syndrome; diagnosis; ultrasound